2012
DOI: 10.17221/208/2011-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

In vitro shoot multiplication as influenced by repeated subculturing of shoots of contemporary fruit rootstocks

Abstract: Vujović T., Ružić Dj., Cerović R., 2012. In vitro shoot multiplication as influenced by repeated subculturing of shoots of contemporary fruit rootstocks. Hort. Sci. (Prague), 39: 101-107.In vitro shoots of vegetative rootstocks for cherry (Gisela 5 and Gisela 6), plum (Fereley Jaspi) and pear (Pyrodwarf ) were repeatedly subcultured for 10 subcultures on Murashige and Skoog medium of unchanged hormonal composition. Shoot formation capacity decreased over repeated subculturing in all genotypes. The first signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 21 publications
3
41
0
2
Order By: Relevance
“…The plants were kept in the glasshouse and 90 per cent survival was obtained after 4 weeks of transfer (Figure 4). It was observed that better root and shoot development prior to hardening determined the survival of in vitro raised plants which is also supported by Minaev et al, (2003) and Vujovic et al, (2012).…”
Section: Hardening and Acclimatizationsupporting
confidence: 66%
“…The plants were kept in the glasshouse and 90 per cent survival was obtained after 4 weeks of transfer (Figure 4). It was observed that better root and shoot development prior to hardening determined the survival of in vitro raised plants which is also supported by Minaev et al, (2003) and Vujovic et al, (2012).…”
Section: Hardening and Acclimatizationsupporting
confidence: 66%
“…Propagation by seeds can generate a large amount of genetic variation in the rootstocks, aff ecting grafting effi ciency and plant yield in the fi eld. On the other hand, cuttings harvested from fi eld plants can also reduce the effi ciency of the grafting process and can spread diseases into the new plantations (Vujović et al, 2012). It is evident, for both the industry and breeders, that tissue culture has the potential to produce rootstocks on a large scale faster than the traditional methods.…”
Section: B Rootstock Micropropagation and Micrografting In Prunus Spmentioning
confidence: 99%
“…Additionally, shoot formation and multiplication rate generally had significantly higher averages in the last subcultivation, thus showing that carrying out five subcultures in the micropropagation of blackberry is possible, without affecting the multiplication rates thereof. This fact contradict Vujović et al (2012), who claim that during in vitro propagation of nodal segments, a decrease of potential shoot growth can be seen in the last subcultures due to successive cuttings, and to the cumulative effect of cytokinins, which, over time, can cause damage to the tissues in cultivation. Thus, the high-multiplication rates obtained in our study show that large-scale propagation of blackberry can be successfully performed, after short and medium-term storage under minimal growth conditions, which is a rare, or nonexistent result in the literature, especially regarding the time of in vitro conservation evaluated without subcultures.…”
mentioning
confidence: 77%
“…However, the successful application of these methods is limited because they require a large area for planting, a great deal of manpower, and intensive weed control, aside from the fact that these species are highly susceptible to diseases and pests (Vujović et al, 2012). Thus, the propagation of blackberry through in vitro cultivation techniques, such as micropropagation from nodal segments, has been increasingly studied.…”
mentioning
confidence: 99%